Enhancing Elementary Students' Opinion Expression Skills Through the Discussion Method in Indonesian Elementary Schools - Stevani David; Efendi Efendi; Pahriadi Pahriadi (CV. Dharma Samakta Edukhatulistiwa, 2025)
The objective of this study was to enhance students' ability to express opinions through the application of the Discussion Method in 5th grade of SD Inpres Tavanjuka. This study employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which consists of four stages: planning, implementation, observation, and reflection. The research was conducted over two cycles. Data were collected through observation and tests administered at the end of each cycle. The findings showed that the classical absorption rate (CAR) for expressing opinions in Cycle I was 71.95%, with a classical learning completeness (CLC) rate of 78.26%. In Cycle II, the results improved, with a CAR of 76.73% and a CLC of 91.30%. Based on the percentage of learning completeness in Cycles I and II, a significant improvement was observed, with an increase of 4.78% in CAR. Thus, it can be concluded that learning through the application of the Discussion Method effectively enhances the ability of 5th grade students at SD Inpres Tavanjuka to express their opinions. The action hypothesis in this study is therefore accepted.